2014
DOI: 10.1111/dmcn.12475
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension in childhood: pitfalls in diagnosis

Abstract: ABBREVIATIONS CSFISCerebrospinal METHOD We reviewed the records of all children referred with symptoms and/or signs consistent with raised intracranial pressure (ICP) and normal magnetic resonance imaging of the brain to our tertiary neurology unit over 4 years. IIH was confirmed after expert ophthalmology including ultrasound/tomography and advanced cerebrospinal fluid (CSF) pressure studies. RESULTSOf 15 children (six males, nine females; median age 12y, range 3-15y), six (five females, one male) were confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In adults and children the assessment of average CSF pressure over more than 20 minutes, 'steady state', is reported to be more reliable than a single opening pressure measurement using the height of a fluid column (34)(35)(36).…”
Section: Diagnosismentioning
confidence: 99%
“…In adults and children the assessment of average CSF pressure over more than 20 minutes, 'steady state', is reported to be more reliable than a single opening pressure measurement using the height of a fluid column (34)(35)(36).…”
Section: Diagnosismentioning
confidence: 99%
“…(22) In adults and children the assessment of average CSF pressure over more than 20 minutes, 'steady state', is reported to be more reliable than a single opening pressure measurement using the height of a fluid column. (23,24,25) Diagnostic errors resulted in overdiagnosis of IIH in 39.5% of patients referred for presumed IIH to a neuro-ophthalmology service of a tertiary center and prompted unnecessary tests, invasive procedures, and missed diagnoses. The most common errors were inaccurate ophthalmoscopic examination in headache patients and thinking biases, reinforcing the need for rapid access to specialists with experience in diagnosing optic nerve disorders.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Although ICP can reach levels that, if not relieved, can cause papilledema leading to optic atrophy and severe visual loss, impaired cognitive function has not been described. 2,44,66,69,87 That is not to say that IIH arising in childhood does not affect NCI-it may not have been looked for, as it has been in a study (in adults) by Yri et al, 88 who found that "patients with IIH performed significantly worse than controls in four of six cognitive domains. .…”
Section: Idiopathic Intracranial Hypertensionmentioning
confidence: 99%